2019
DOI: 10.1680/jgeot.16.p.325
|View full text |Cite
|
Sign up to set email alerts
|

Rigid pile response to cyclic lateral loading: laboratory tests

Abstract: This paper presents experimental work aimed at improving understanding of the behaviour of rigid monopiles, in cohesionless soils, subjected to lateral cyclic loading. It involves 1g laboratory model tests, scaled to represent monopile foundations for offshore wind turbines. The test programme is designed to identify the key mechanisms governing pile response, and is divided into four main parts: (a) investigation of loading rate effects; (b) hysteretic behaviour during unloading and reloading; (c) pile respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…Results from laboratory tests provide fundamental insights on the foundation behaviour that determine the form of development of theoretical and numerical models. The work published by Abadie, Byrne [1,3] and Abadie [21] involves laboratory floor model tests, scaled to represent a full-scale wind-turbine monopile in drained sand, and elaborates clearly the important effects that need to be accounted for in detailed modelling:…”
Section: Objective Cyclic Behaviour: Experimental Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…Results from laboratory tests provide fundamental insights on the foundation behaviour that determine the form of development of theoretical and numerical models. The work published by Abadie, Byrne [1,3] and Abadie [21] involves laboratory floor model tests, scaled to represent a full-scale wind-turbine monopile in drained sand, and elaborates clearly the important effects that need to be accounted for in detailed modelling:…”
Section: Objective Cyclic Behaviour: Experimental Evidencementioning
confidence: 99%
“…The tests considered here were performed in dry sand, reproducing drained loading offshore. In these conditions, Abadie et al [1] showed that rate effects can be neglected, allowing a focus on the development of a modelling method for ratcheting. This is a step towards a comprehensive modelling framework for offshore monopile design.…”
Section: Objective Cyclic Behaviour: Experimental Evidencementioning
confidence: 99%
See 3 more Smart Citations